1985
DOI: 10.1111/j.1476-5381.1985.tb08938.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the histamine receptor in the isolated muscularis mucosae of the guinea‐pig oesophagus

Abstract: 1 To characterize the histamine receptors in the muscularis mucosae, the isotonic responsiveness of the isolated muscularis mucosae of the guinea-pig oesophagus to histamine receptor agonists and antagonists was examined in vitro. 2 Histamine (0.1-100 M) produced a concentration-dependent contraction of the muscularis mucosae (EC50 = 1.6 ± 0.2 LM). The contractions were rapid in onset, sustained, reversible by washing and the preparation did not show tachyphylaxis. 3 2-Methylhistamine (2-MH), 2-pyridylethylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In contrast to external smooth muscles, the muscularis mucosae responded to contraction by the application of arachidonic acid and its metabolites, where leukotriene C4 and D4 were the most potent, followed by PGE2, and the least by PGF2α and PGI2 (Kamikawa and Shimo, 1979b;Kamikawa et al, 1985a). We have also demonstrated the homogeneous populations of excitatory histamine H1-receptors in the muscularis mucosae of the guinea-pig esophagus (Fujinuma et al, 1985). The H1-receptors are partly linked with the stimulation of endogenous PG biosynthesis or of intramural cholinergic nerves.…”
Section: Responsiveness To Drugsmentioning
confidence: 79%
“…In contrast to external smooth muscles, the muscularis mucosae responded to contraction by the application of arachidonic acid and its metabolites, where leukotriene C4 and D4 were the most potent, followed by PGE2, and the least by PGF2α and PGI2 (Kamikawa and Shimo, 1979b;Kamikawa et al, 1985a). We have also demonstrated the homogeneous populations of excitatory histamine H1-receptors in the muscularis mucosae of the guinea-pig esophagus (Fujinuma et al, 1985). The H1-receptors are partly linked with the stimulation of endogenous PG biosynthesis or of intramural cholinergic nerves.…”
Section: Responsiveness To Drugsmentioning
confidence: 79%
“…The oesophageal muscularis mucosae is innervated chie¯y by excitatory cholinergic nerves and sparsely by inhibitory adrenergic nerves, but not by non-adrenergic and non-cholinergic nerves (Kamikawa & Shimo, 1979;Kamikawa et al, 1982). It is already known that the receptor systems in this tissue for catecholamines, 5-hydroxytryptamine, acetylcholine and histamine are dierent from those in the external smooth muscles (Uchida, 1983;Uchida et al, 1983;Kamikawa et al, 1985;Fujinuma et al, 1985). ET-1 elicits contractions of the isolated oesophageal muscularis mucosae, but the receptor mechanisms and subtypes involved in this eect are still uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…The receptor-mediated contraction of the esophageal muscularis mucosae presumably links with the receptoractivated Ca 2+ influx pathway [1][2][3][4]. Recently, we have reported that exogenously applied BaCl 2 selectively inhibits the receptor-mediated contraction of the guinea pig esophageal muscularis mucosae [5].…”
Section: Introductionmentioning
confidence: 99%